Televizyonda Dinsel Siyaset: Dini İçerikli Dizilerin Kamusal Alan Projesinde Kadın veya Erkek Olmak - Çağlar Enneli (Alternatif Politika)
In this study, I will argue for the critical value of politics of representation in a current time that witnesses rapid development in electronic communication mediums together with significant transitions in conceptualization of public sphere. Contradiction between powers of modernization and traditional/religious forces somehow thought to be explanatory framework of Turkish politics finds its correspondence in this period of transition in public sphere as well. Rise of religious politics to the extent that its representative political parties continuously get more and more powerful in leading Turkish governance has been debated in various resources. These debates on the one hand concerns with negative effects of the rise of religious politics on the Turkish modernization process rooted as old as 19th century and on the other hand criticizes the top-down nature of the modernization politics by suggesting that no matter what any politics that does not regard the beliefs and thoughts of society would be failed sooner or later. Both sides of the debate, however, have shared a common attitude in focusing only institutional election results in evaluating the success of religious politics. In the lack of analysis of social resources of religious politics, conservatism of society has become a common paraphrase in debates. Taking a different step, I will provide data from the study I conducted on religious-based television programs between 2005 and 2007 that will aid to inquire whether the religious politics based on television representations strengthens institutional religious politics. Analyzing appearances and representation of gender in religious-based television programs of Kanal 7 and Samanyolu TV channels, both of which are markedly religious in broadcasting, I will ask for how public sphere created in Islamic politics of representation deals with the social differences.